Evaluasi Kebijakan Tunjangan Kinerja Daerah Di Badan Pelayanan Perizinan Terpadu Kota Manado - Wuaten, Theo B. W.; Ruru, Jorry M (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: This study aimed to evaluate whether the TKD policy has been implemented properly, and the extent to which performance (outcomes and impact) the allowance policy in improving the performance of employees in the Integrated Licensing Service Agency of Manado. The method used in this study is a qualitative method. Research informants set as many as 12 people were taken from the Agency leadership elements, structural officials and staff personnel at the Integrated Licensing Service Agency of Manado. Data collection methods / techniques interview. The analysis technique used is the qualitative analysis of interactive models. Based on the results of the study concluded: (1) Implementation of policies TKD has been conducted in accordance with established policy, especially the provision of benefits recipients criteria, assessment component of the calculation of benefits, payment calculations and benchmarks. (2) Policy TKD has given results and positive impact in improving employee performance and discipline. Departing from the results of the study suggested that TKD policy or administration PNSD TPP to Manado City needs to continue, by improving the weaknesses that exist. Keywords: policy evaluation, regional performance benefits